Principle of Impartiality: Air Transport Restriction Policy During the Covid-19 Pandemic in Indonesia - Y, Annalisa; Murzal, Murzal; Muntaqo, Firman; Syaifuddin, M. (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 11 No 2 (2022), 2022)
The aim of this study is to analyze and identify policies issued by the government related to air passenger transportation restrictions during the Covid-19 pandemic. In addition, this study also examines the application of the principle of impartiality to passengers and airlines in the policy. This study uses a normative research method with secondary data in the form of a Circular issued by the Minister of Transportation and the Task Force for the Acceleration of Handling Covid-19 from 2020 to 2021. The results show that the policies issued by the Minister of Transportation during the Covid-19 Pandemic are by limiting the number of passengers ranging from 50% to 70% of the carrying capacity was made based on policies in order to minimize the transmission of Covid-19 passengers in the aircraft cabin by applying the principle of social distancing. The policy regulations issued are in the form of a Circular from the Ministry of Transportation and the Covid-19 Handling Acceleration Task Force related to passenger restrictions while still paying attention to the principle of impartiality. This restriction is an appropriate action, not discriminatory treatment for airlines where restrictions on passenger transportation can have an effect on reducing revenue. However, the restriction policy is implemented in the context of the state protecting the health of its citizens (passengers).